Smoking practices among fourth year students of Tarlac High School, class 1970-1971 - Primero, Begonia P. 1917- (1971)
This study aimed to find out the smoking practices of the fourth year students of the Tarlac High School, Division of Tarlac, Class 1970-71. The normative survey was employed. Out of the 640 students who participated in this study, only 175 boys were found to be smokers. On the basis of the findings, it was concluded that a good number of the fourth year boys smoked cigarettes while not one of the girls smoked, that smoking among the boys started as early as primary grades, that the smokers started smoking through the influence of their peers and the majority of their practices were unhealthy. Smoking education should be taught as early as the primary grades up to the college level.